Diet Gizi Diabetes Melitus Pada Lansia Di Puskesmas Mojosari Kabupaten Mojokerto - Atik Sri Wulandari; Popharina Berlianda; Agshal Almachzumi Andili; I Gede Paskha Yustiana; Komang Kuntari; Nabhila Annisa Rizqi N A; Tansatrisna Vony Rei Siswanto; Muhammad Rifky Ramadhan; Wike Herawaty; Nur Khamidah (Jurnal Riset Multidisiplin Edukasi, 2026)
Background: Diabetes Mellitus (DM) in the elderly is a significant public health issue due to the risk of complications and decreased quality of life resulting from physiological changes and inappropriate nutritional intake. In the Mojosari Community Health Center area, the level of understanding and compliance of the elderly toward medical nutrition therapy is often still low. Objective: This activity aimed to increase the knowledge, awareness, and ability of the elderly and their families to manage DM nutritional diets independently and sustainably. Methods: The counseling was conducted on February 13, 2026, at the Mojosari Community Health Center, involving 25 participants (elderly and caregivers). The intervention method utilized face-to-face education, audio-visual presentations, and the distribution of leaflets focusing on the 3J diet principles (Schedule, Amount, Type). Evaluation was performed using pre-test and post-test instruments. Results: There was a significant increase in knowledge, marked by a rise in the average score from 57 to 88. Furthermore, the number of participants in the "Good" knowledge category increased from 16% to 80% following the intervention. Conclusion: This counseling activity was effective in improving participants' health literacy regarding DM diet management and complication prevention in the geriatric population.